2007
DOI: 10.1039/b705461k
|View full text |Cite
|
Sign up to set email alerts
|

Milestones in the development of photodynamic therapy and fluorescence diagnosis

Abstract: Many reviews on PDT have been published. This field is now so large, and embraces so many sub-specialties, from laser technology and optical penetration through diffusing media to a number of medical fields including dermatology, gastroenterology, ophthalmology, blood sterilization and treatment of microbial-viral diseases, that it is impossible to cover all aspects in a single review. Here, we will concentrate on a few basic aspects, all important for the route of development leading PDT to its present state:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
197
0
14

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(215 citation statements)
references
References 228 publications
4
197
0
14
Order By: Relevance
“…The active drug forms reactive oxygen species such as singlet oxygen to kill cells. Various agents, including porphyrins and phthalocyanines, have been examined as photosensitizers (21)(22)(23). Most photosensitizers are fluorescent and some can emit NIR light that can be used for in vivo imaging to identify the location of cancer cells and provide image-guided PDT treatment, potentially leading to improved therapeutic accuracy and outcome (21).…”
Section: Introductionmentioning
confidence: 99%
“…The active drug forms reactive oxygen species such as singlet oxygen to kill cells. Various agents, including porphyrins and phthalocyanines, have been examined as photosensitizers (21)(22)(23). Most photosensitizers are fluorescent and some can emit NIR light that can be used for in vivo imaging to identify the location of cancer cells and provide image-guided PDT treatment, potentially leading to improved therapeutic accuracy and outcome (21).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, four main classes of PS -porphyrin derivatives, chlorins, porphycenes, and phthalocyanineshave been approved by the US Food and Drug Administration for the clinical treatment of cancer. 26,27 Among these, zinc phthalocyanine (ZnPc) exhibit a high photodynamic effect, as it possesses a diamagnetic Zn(II) central metal ion whose d-shell is fully occupied, by which the yield of triplet excited state and the long life essential for the generation of ROS becomes high. 28 Moreover, ZnPc has a large absorption cross section of light at the tissue-penetrating spectral range of 650-900 nm.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] With high tumor avidity, the chlorin-based compound 2-(1-hexyloxyethyl)-2-devinyl pyropheophorbide-a (HPPH) has been shown to be a potential photosenstizer for imaging and treatment. 4 Recent HPPH-oriented laboratory research and early-phase clinical studies at Roswell Park Cancer Institute (RPCI) have demonstrated that HPPH-mediated PDT is an effective treatment option for superficial cancers such as skin and head and neck lesions in the oral cavity.…”
Section: Introductionmentioning
confidence: 99%